Assessment of Knowledge Regarding Risks and Benefits of the Use of Non-Vitamin K Antagonist Oral Anticoagulants. (August 2022) - Valery, Jose Raul; Marar, Ahmad; Pujalte, George; Ward, Cynthia; Abdelmoneim, Yousif M.; Fitzgerald, Patrick J.; Mwakyanjala, Edson; Harris, Dana M.; Murray, Loren; Heckman, Michael G.; White, Launia J.; Stancampiano, Fernando
Background: Non-vitamin K antagonist oral anticoagulants (NOAC) have replaced vitamin K antagonist (VKA) oral anticoagulants as the first-line treatment option for stroke prevention in high-risk patients with atrial fibrillation. With VKA therapy, disease and treatment-related knowledge is associated with improved adherence and outcomes. There is concern that due to the lack of need for ongoing visits for laboratory monitoring in patients on NOACs, there is less opportunity for education, leading to poor disease- and treatment-related knowledge in this patient group. Methods: One hundred ninety-nine (199) patients presenting to 2 primary care clinics on NOAC therapy were surveyed regarding atrial fibrillation and their knowledge regarding NOACs. Chart review was completed to determine patient characteristics and data obtained was compared with survey results to determine the accuracy of the survey responses. Results: Patients with a lower degree of NOAC knowledge tended to be older ( P < .001), have higher Charlson Comorbidity Index scores ( P = .001), use apixaban more often ( P = .008), and have been on NOACs for a shorter time period ( P = .007). Conclusions: There is an opportunity to improve NOAC-related knowledge in patients with atrial fibrillation. When developing educational interventions, patient characteristics associated with poor knowledge should be considered. Based on our results, these are patients who are older, more medically complex, are on apixaban, and have been on NOAC therapy for a shorter duration.